Strategic leadership and inter-firm knowledge sharing : foundations for effective digital transformation and customer engagement - Usman, Muhammad; Zahoor, Nadia; Akhtar, Muhammad Waheed; Bani-Melhem, Shaker (Emerald, 2025)
Purpose The purpose of this paper is to examine how strategic leadership and inter-firm sharing lead to digital transformation and customer engagement. Design/methodology/approach Time-lagged data were collected from CEOs and customers of multinational organizations operating in China. Data were analyzed using structural equation modeling in Mplus (8.8). Findings The results from the structural model indicate that strategic leadership positively impacts digital transformation, which subsequently enhances CE behavior. Furthermore, inter-firm knowledge sharing strengthens the relationship between strategic leadership and digital transformation, highlighting its role as a critical enabler in fostering CE. Originality/value This study brings to the fore crucial yet overlooked roles of strategic leadership and inter-firm knowledge sharing in shaping organizations’ digital transformation and CE. It develops a framework for multinational organizations aiming to enhance.
Keywords: Strategic leadership; Digital transformation; Inter-firm knowledge sharing; Customer engagement